Brain MR Imaging and 1H-MR Spectroscopy Changes in Patients with Extrahepatic Portal Vein Obstruction from Early Childhood to Adulthood - Yadav, S.K.; Saksena, S.; Srivastava, Anshu; Srivastava, Arti; Saraswat, V.A.; Thomas, M.A.; Rathore, R.K.S.; Gupta, R.K. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: MR imaging and 1H-MR spectroscopy changes are well reported in cirrhotic patients, whereas they are inadequately reported in EHPVO. The aim of this study was to investigate age-related changes in brain MR imaging and metabolite profile in EHPVO with and without MHE and to explore any correlation of imaging and 1H-MR spectroscopy parameters with blood ammonia. MATERIALS AND METHODS: Sixty-three patients with EHPVO (children, 7–12 years [n = 22], adolescents, 13–18 years [n = 15] and adults, 19–41 years [n = 26]) and 47 healthy age/sex-matched volunteers were studied. Neuropsychological tests, MR imaging, 1H-MR spectroscopy, and blood ammonia estimation were performed in all subjects. RESULTS: Of 63 EHPVO patients, 25 (40%) who had MHE showed significantly increased MD, Glx, and blood ammonia in all 3 age groups; however, myo-inositol was significantly lower only in adults when compared with controls. MD positively correlated with blood ammonia and Glx in all age groups. Brain choline levels were normal in all patients with different age groups. CONCLUSIONS: Increases in brain MD, Glx, and blood ammonia were associated with MHE in all age groups. Normal brain choline in EHPVO signifies healthy liver and may serve as a diagnostic marker for its differentiation from cirrhosis-induced encephalopathy. Significant decrease of myo-inositol in adults is probably due to cellular osmoregulation secondary to long-standing hyperammonemia. ALICanterior limb of internal capsuleALTalanine transaminaseANOVAanalysis of varianceASTaspartate transaminaseBAblood ammoniaCGcingulate gyrusCNcaudate nucleusDTIdiffusion tensor imagingEHPVOextrahepatic portal vein obstructionFAfractional anisotropyFWMfrontal white matterGlxglutamine/glutamateGPglobus pallidus1H-MRS1H-MR spectroscopyMDmean diffusivityMHEminimal hepatic encephalopathyNAAN-acetylaspartateNSnot significantOWMoccipital white matterPputamenPLICposterior limb of internal capsulePTprothrombin timeSsignificantSBserum bilirubinSpspleniumTthalamus